From the Edge to the Cloud: Model Serving in ML.NET. - Lee, Yunseong; Scolari, Alberto; Chun, Byung-Gon; Interlandi, Matteo; Weimer, Markus (IEEE Data(base) Engineering Bulletin, 2018)
As Machine Learning (ML) is becoming ubiquitously used within applications, developers need effective solutions to build and deploy their ML models across a large set of scenarios, from IoT devices to the cloud. Unfortunately, the current state of the art in model serving suggests to deliver predictions by running models in containers. While this solution eases the operationalization of models, we observed that it is not flexible enough to address the variety of ML scenarios encountered in large companies such as Microsoft. In this paper, we will overview ML.NET—a recently open sourced ML pipeline framework— and describe how ML models written in ML.NET can be seamlessly integrated into applications. Finally, we will discuss how model serving can be cast to a database problem, and provide insights on our recent experience in building a database optimizer for ML.NET pipelines.